2021
DOI: 10.3390/v13101961
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Epidemiology and Genetic Diversity in Leipzig, Germany during 2013–2017

Abstract: Globally and in all age groups, noroviruses are a main cause of gastroenteritis. To assess their local epidemiology and genetic diversity, stool samples of 7509 inpatients with gastrointestinal complaints from all age groups were analyzed. After detection of norovirus genogroup I and II RNA by real-time RT-PCR, viral capsids were genotyped by partial nucleic acid sequencing. In the case of GII.2 strains, polymerase genotypes were also assessed. Between October 2013 and September 2017, presence of norovirus RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
3
4
0
Order By: Relevance
“…In Brazil, previous studies performed in other regions (Northern and Northeastern regions) have demonstrated norovirus detection rates varying from 11% to 35.2% in medically attended and hospitalized children with AGE [36][37][38]. In our study, as expected, the GII genotypes predominated among the infections, in line with several studies performed elsewhere, where norovirus GII detection rates varied from 70% to 93.6% among AGE cases [39][40][41]. During norovirus outbreaks reported in Catalonia, Spain from 2017 to 2019 in closed and semi-closed settings, GII was the predominant genogroup, being involved in 70% of outbreaks [31].…”
Section: Discussionsupporting
confidence: 92%
“…In Brazil, previous studies performed in other regions (Northern and Northeastern regions) have demonstrated norovirus detection rates varying from 11% to 35.2% in medically attended and hospitalized children with AGE [36][37][38]. In our study, as expected, the GII genotypes predominated among the infections, in line with several studies performed elsewhere, where norovirus GII detection rates varied from 70% to 93.6% among AGE cases [39][40][41]. During norovirus outbreaks reported in Catalonia, Spain from 2017 to 2019 in closed and semi-closed settings, GII was the predominant genogroup, being involved in 70% of outbreaks [31].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous global studies, this study identified GII NoV as the most predominant genogroup in Shanghai ( Kendra et al., 2022 ). However, the detection rate of GI NoV in Shanghai was much lower than that in Congo (13.0%), Germany (6.2%) and Indonesia (3.4%) ( Mikounou Louya et al., 2019 ; Ennuschat et al., 2021 ; Utsumi et al., 2021 ). This suggests that there are significant geographical differences in the prevalence of GI NoV. As GI NoV plays an important role in the occurrence of NoV outbreaks, the epidemiology of GI NoV in Shanghai needs to be closely monitored in the future.…”
Section: Discussionmentioning
confidence: 81%
“…In Japan and South Korea [ 24 , 25 ], similar to Beijing and various Chinese provinces [ 22 , 26 ], outbreaks generally occur in childcare centers and schools. However, in developed countries, norovirus outbreaks mainly occur in healthcare facilities, [ 2 , 11 , 27 , 28 ], which may reflect the differences in the sensitivity and coverage among surveillance systems. A specific norovirus surveillance system has not been established for healthcare facilities in China [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main symptoms of norovirus infections are vomiting and diarrhea, which are usually self-limiting and of 1 to 3 days’ duration [ 10 ]. However, older populations, immunocompromised individuals, and children younger than 5 years may suffer from severe or prolonged illness [ 11 ]. Outbreaks caused by norovirus are often reported in schools, kindergartens, hospitals, restaurants, and daily care centers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%